Clothes Market in Uzbekistan: Competitive Environment, Development - Askarova Mavluda Turapovna (Research Parks Publishing LLC, 2019)
The article explores the status and development of the apparel market in Uzbekistan, and changes in itsstructure based on marketing research and evaluates the impact of changes in the retail segment of the apparel market, the composition of the consumer market of garments, and the changes in consumer segment. Changes in consumption by squeezing a range of competing countries from the domestic market are studied on the basis of the panel research method, and the matrixof factors that influence its formation and the shape of the wardrobe.